2017
DOI: 10.18632/oncotarget.15714
|View full text |Cite
|
Sign up to set email alerts
|

Sodium butyrate improves porcine host defense peptide expression and relieves the inflammatory response upon toll-like receptor 2 activation and histone deacetylase inhibition in porcine kidney cells

Abstract: Host defense peptides (HDPs) are an important component of the innate immune system and possess direct antimicrobial and immunomodulatory activities. Dietary regulation of HDPs synthesis has emerged as a novel non-antibiotic approach to combat pathogen infection. There are species- and tissue-dependent characteristics of the regulation and mechanism of HDPs. In this study, we investigated whether the histone deacetylase inhibitor (HDACi) sodium butyrate (NaB) could induce HDP expression and the mechanism under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 49 publications
2
20
0
Order By: Relevance
“…Upregulation of pBD2 in response to L. plantarum ZLP001 likely inhibited pathogenic bacteria in our study, as reported previously that pBD2 protects against a wide range of pathogenic bacteria in vitro ( Veldhuizen et al, 2007 ; Zhang et al, 2011 ; Deng et al, 2013 ). pBD3 exhibits not only profound antimicrobial properties, but also strong immunoregulatory ability by regulating the expression of the proinflammatory cytokine IL-8 ( Dou et al, 2017 ). In the present study, pBD3 mRNA expression was considerably increased only at the highest concentration of L. plantarum ZLP001, which was inconsistent with another report of high pBD3 expression at 10 7 and 10 8 CFU/mL ( Liu et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Upregulation of pBD2 in response to L. plantarum ZLP001 likely inhibited pathogenic bacteria in our study, as reported previously that pBD2 protects against a wide range of pathogenic bacteria in vitro ( Veldhuizen et al, 2007 ; Zhang et al, 2011 ; Deng et al, 2013 ). pBD3 exhibits not only profound antimicrobial properties, but also strong immunoregulatory ability by regulating the expression of the proinflammatory cytokine IL-8 ( Dou et al, 2017 ). In the present study, pBD3 mRNA expression was considerably increased only at the highest concentration of L. plantarum ZLP001, which was inconsistent with another report of high pBD3 expression at 10 7 and 10 8 CFU/mL ( Liu et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Butyrate, an important energy source for intestinal epithelial cells, has been shown to stimulate growth of small intestinal epithelium and maintain intestinal homeostasis. The effects of butyrate on oxidative stress, inflammation [39], and intestinal barrier function [40] have been described, particularly its activities in promoting gut health both in vitro [41] and in vivo [42]. In addition, previous studies reported that butyrate decreased diarrhea incidence in post-weaning piglets [42] and congenital chloride diarrhea children [43].…”
Section: Discussionmentioning
confidence: 99%
“…Each sample reaction was run in duplicate on the same plate. The gene-specific primers are presented in Table 1 (1416). The mRNA expression levels were determined using the 2 −ΔΔCt method with β-actin as a reference.…”
Section: Methodsmentioning
confidence: 99%